Handover optimization in cross tier LTE heterogeneous networks / Mohd Saufi Nasro Ali - Nasro Ali, Mohd Saufi (2019)
In this modern era, the current mobile network technology focuses on the Long Term Evolution (LTE) network deployment. The deployment concentrates on the design that further increases the optimization or parameter changes of network capacity and coverage. Since its early adoption within Malaysia, it has become one of the important parts for every mobile user that uses system consisting of heterogeneous network.